(untitled) (Public Sector Economics - submission site, 2022)
This paper analyzes fiscal policy sustainability and cyclicality in Croatia. The main novelty of the paper is that our fiscal response function allows for asymmetric behavior over the business cycle. We allow fiscal policy sustainability and cyclicality to differ across the expansionary and recessionary regimes. The overall results suggest that fiscal policy in Croatia is both sustainable and countercyclical. We find evidence of asymmetric behavior of fiscal policy cyclicality. In the expansionary regime, fiscal policy is countercyclical, while in the recessionary regime, it varies between procyclical and acyclical. On the other hand, we find only limited evidence of asymmetric behavior of public debt sustainability. During good times, Croatian policymakers try to keep fiscal policy both sustainable and countercyclical, which is required fiscal policy behavior. In recessionary times, the characteristics of fiscal policy are not so clear, but tend to be procyclical or acyclical.